KOMNAS HAM: SUATU UPAYA PENEGAKAN HAM DI INDONESIA - Nawawi, Asror (Fakultas Hukum Universitas Bangka Belitung, 2017)
The existence of the National Human Rights Commission (Komnas HAM) does not seem to have functioned optimally. Komnas HAM as always appears late in the enforcement and respect of human rights. The National Human Rights Commission should not only emerge after the violation of Human Rights but also appear as a shield to stem the rate of human rights violations by conducting a series of efforts in the form of socialization concerning the understanding of Human Rights